Random missing tooth error detection in crankshaft function of an engine control unit - Abd Rahman, Fatimah; Gomes, Amesh Eromal; Kamsani, Noor Ain; Mohd Sidek, Roslina; Hashim, Shaiful Jahari; Rokhani, Fakhrul Zaman; Zamali, Mohd Suffian; Ali, Farhan Mohamed (Universiti Malaysia Pahang, 2020)
Automotive industry is migrating to electronic based control which has promoted the evaluation and enhancement of engine control performance using electronic components in the research field. Modern engines are controlled by Engine Control Unit (ECU) where not only functions and control systems are in placed, but also the fail-safe mechanisms must be integrated in the ECU to ensure user safety when an error occurred. This work focuses on developing a reliable crankshaft function in an ECU using field-programmable gate array (FPGA). ABa test is carried out and the number of occurrences at unintended location are being monitored in the system to detect the random missing tooth. The reliability of the function is tested by evaluating response of the crankshaft function in an ECU when an unexpected missing tooth occurs during its operation. The developed system is able to detect the random missing tooth on a crank trigger wheel at an accuracy of 100% when the wheel is on a run at a constant wheel rotational speed. It also flags error message for further processing in other functional units of the ECU as a safe-fail mechanism for the system. Implementation of the random missing tooth detection in the crankshaft function is shown to work in the system which is developed using Verilog code.